90 Years’ Anniversary of Mykola S. Pushkar (03.08.1930 – 21.07.1995) - Problems of Cryobiology; Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 299–300